2017
DOI: 10.1016/j.biopsych.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

CB 1 Cannabinoid Receptors Mediate Cognitive Deficits and Structural Plasticity Changes During Nicotine Withdrawal

Abstract: These findings underline the interest of CBR as a target to improve cognitive performance during early nicotine withdrawal. Cognitive deficits in early abstinence are associated with increased relapse risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 58 publications
6
31
0
Order By: Relevance
“…All drugs were administered in a volume of 10ml per kg of body weight. Doses of nicotine, mecamylamine, cannabidiol and indomethacin were based on previous studies (Ren et al, 2009;Ho et al, 2015;Saravia et al, 2017;Stern et al, 2017).…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…All drugs were administered in a volume of 10ml per kg of body weight. Doses of nicotine, mecamylamine, cannabidiol and indomethacin were based on previous studies (Ren et al, 2009;Ho et al, 2015;Saravia et al, 2017;Stern et al, 2017).…”
Section: Drugsmentioning
confidence: 99%
“…Fourteen days after minipump implantation, nicotine withdrawal syndrome was precipitated by the administration of the nicotinic receptor antagonist mecamylamine (2mg/kg). Systemic administration of mecamylamine in nicotine-treated rodents is a wellestablished model to study the neurobiological mechanisms involved in the different aspects that characterize the nicotine withdrawal syndrome (Muldoon et al, 2015;Qi et al, 2015;Parikh et al, 2016;Saravia et al, 2017), typically observed in abstinent smokers.…”
Section: Nicotine Treatment and Withdrawalmentioning
confidence: 99%
“…One of the endogenous ligands for the cannabinoid receptor (i.e., CB1R) (Saravia et al ., ) has been associated with cognitive deficits in memory and attention that emerge during early abstinence from smoking. In humans, these early cognitive impairments predict early relapse to smoking (Patterson et al ., ).…”
Section: Smoking Cessation and Relapsementioning
confidence: 99%
“…Two different models of stress-induced relapse to nicotine demonstrate the requisite involvement of neuropeptides: corticotropin-releasing factor in the central nucleus of amygdala in reinstatement of operant nicotine seeking (Bruijnzeel et al, 2009); dynorphin and kappa opioid receptors in basolateral nucleus of amygdala in conditioned place preference for nicotine (Nygard et al, 2016). One of the endogenous ligands for the cannabinoid receptor (i.e., CB1R) (Saravia et al, 2017) has been associated with cognitive deficits in memory and attention that emerge during early abstinence from smoking. In humans, these early cognitive impairments predict early relapse to smoking (Patterson et al, 2010).…”
Section: Animal Genetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation